PENDEKATAN COGNITIVE BEHAVIORAL THERAPY (CBT) DALAM KONSELING KELOMPOK UNTUK MENGATASI KECEMASAN AKADEMIK DALAM PENYELESAIAN TUGAS AKHIR MAHASISWA - Lita Fitara Cania; Netrawati; Yeni (Jurnal Ilmu Pendidikan dan Sosial, 2023)
Some students in the last semester experience a lot of academic anxiety in completing their final assignment, because some final students, be it looking for titles, reading references, facing supervisors, facing thesis exams, always feel afraid so that the fear they always feel will make their actions negative or irrational. group counseling approaches that exist in guidance and counseling. The Cognitive Behavioral Therapy (CBT) Approach in Group Counseling changes negative perceptions or ways of thinking and acting to be better and more focused. The purpose of writing this article is so that students in completing their final assignment do not experience academic anxiety and students can change their negative perceptions where students will think in a positive direction, and the final assignment can be completed properly. Writing this article uses literature review or also called literature review. The literature is a description or description of the literature that is relevant to a particular field or topic. The results of the literature review show that with the Cognitive Behavioral Therapy (CBT) approach in group counseling students will have a positive perception and are always enthusiastic and motivated to pass quickly in completing their thesis or final assignment so that Academic anxiety experienced by students will be resolved.